2017
DOI: 10.3233/jad-170477
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Chuan and Baduanjin Increase Grey Matter Volume in Older Adults: A Brain Imaging Study

Abstract: The aim of this study is to investigate and compare how 12-weeks of Tai Chi Chuan and Baduanjin exercise can modulate brain structure and memory function in older adults. Magnetic Resonance Imaging(MRI) and memory function measurements (Wechsler Memory Scale-Chinese revised, WMS-CR)were applied at both the beginning and end of the study. Results showed that both Tai Chi Chuan and Baduanjin could significantly increase grey matter volume (GMV) in the insula, medial temporal lobe (MTL), and putamen after 12-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 93 publications
5
110
1
2
Order By: Relevance
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 32 randomized clinical trials with 3624 participants were included in the analysis. The age of the included participants ranged from 50 to 85 years.…”
Section: Resultsmentioning
confidence: 99%
“…Because mind‐body exercise is a nonpharmacologic therapy, nearly all of the studies failed to blind the participants and personnel. The outcome assessments were blinded in 20 studies (62.5%) . Thirty studies (93.75%) had a low risk of attrition bias because most studies reported the dropout rate or represented detailed explanations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations